Robust active steering control for vehicle rollover prevention. (29th August 2019) - Shao, Ke; Zheng, Jinchuan; Huang, Kang
This paper presents a dynamic vehicle rollover model and robust controller for rollover prevention by using a steer-by-wire (SbW) system. Firstly, a linear vehicle dynamic model is derived whose behaviours vary as a function of the time-varying vehicle speed. Next, a load transfer ratio (LTR) model is proposed for measuring the rollover conditions in a vehicle. In particular, the LTR model is generalised based on the conventional one by explicitly considering the rolling motion of sprung mass. Moreover, the relationship of LTR between steering angle and vehicle speed is analysed. To prevent the undesired rollovers, a sliding mode control (SMC) approach is then utilised to design the robust controller for rollover prevention. Finally, simulation results are shown to verify the efficiency of rollover prevention under the proposed controller and its robustness against the vehicle speed and vehicle parameter variations.